Formulation of Hairspray from Cherry Leaves (Muntingia calabura L.) with Antimicrobial Properties - Reynelda Juliani Sagala; Pretty Falena Atmanda Kambira; Karmil Tri Nanda (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Introduction: Indonesia is a tropical country with high temperatures and humidity. Poor personal hygiene can trigger bacteria to grow and multiply. According to research, bacteria that are usually found in skin and hair including Staphylococcus aureus (37%), followed by Escherichia coli (17%). Use of antibacterial hairspray is expected to inhibit the growth of pathogenic bacteria on the surface of the scalp and hair. Using natural ingredients, i.e., cherry (Muntingia calabura L.) leaves, in the form of antibacterial hairspray preparations, is expected not to irritate the scalp, be more eco-friendly, and the raw materials are easily obtained. Methods: The preparation of cherry (Muntingia calabura L.) leaves extract was carried out by maceration method with 70% ethanol (simplisia : solvent = 1:10). Furthermore, the extract was then evaluated for phytochemical content, formulation optimization, and antibacterial activity. Afterward, formulation and preparation, and lastly, its evaluation in the form of an organoleptic test, pH test, viscosity test, homogeneity test, spreadability test, adhesion test, and product stability test. Results: The results of phytochemical screening of flavonoid compounds and tannins from cherry (Muntingia calabura L.) leaves extract resulted in a positive reaction. The minimum inhibitory level of cherry (Muntingia calabura L.) leaves extract against Staphylococcus aureus and Escherichia coli bacteria was 40 mg/ml. Cherry (Muntingia calabura L.) leaves extract was then formulated into hairspray dosage forms with different concentrations of extract in Formula A (0.1%), Formula B (0.3%), and Formula C (0.5%). Conclusions: The hairspray formula that had the best stability after passing the freeze-thaw cycling test and physical evaluation of the preparation during storage for 28 days was Formula C. The parameters of the observed hairspray were organoleptic, pH, homogeneity, viscosity, spreadability, and adhesion. Keywords: Hairspray - Cherry Leaves – Stability - Antibacterial